Respuesta :

Answer:

Step-by-step explanation:

a). [tex]\text{cos}^4(\frac{\theta}{6})-\text{sin}^4(\frac{\theta}{6})=\text{cos}\frac{\theta}{3}[/tex]

   By solving left hand side of the equation,

   = [tex][\text{cos}^2(\frac{\theta}{6})-\text{sin}^2(\frac{\theta}{6})][\text{cos}^2(\frac{\theta}{6})+\text{sin}^2(\frac{\theta}{6})][/tex]

   = [tex][\text{cos}^2(\frac{\theta}{6})-\text{sin}^2(\frac{\theta}{6})](1)[/tex] [Since, cos²a + sin²a = 1]

   = [tex]\text{cos}\frac{\theta}{3}[/tex] [Identity used → cos²a - sin²a = cos(2a)]

Hence, left hand side of the given equation = Left hand side of the equation.

ACCESS MORE